1995
DOI: 10.1111/j.1439-0523.1995.tb00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of karnal bunt resistance in 14 Mexican bread‐wheat genotypes

Abstract: Fourteen Mexican genotypes of bread wheat {Triticum aestivum L.) with good to moderate levels of resistance to Karnal bunt {Tilletia indica (Mitra)) were crossed with the highly susceptible cultivar WL711 to determine the genetic basis of resistance. The parents, F,, Fj and backcross populations of the 14 crosses were evaluated under artificial epiphytotic conditions during the 1993-94 season for Karnal bunt resistance. The Fi data suggested that the resistance was dominant to partially dominant over susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Previous genetic studies on KB resistance in wheat indicated that one to six major genes condition resistance in various wheat germplasms (Morgunov et al 1994;Fuentes-Dávila et al 1995;Singh et al 1995aSingh et al , b, 1999Villareal et al 1995). Six wheat chromosomes (1D, 2A, 3B, 3D, 5D and 7A) were identified as influencing reaction to the pathogen (Gill et al1993;Singh et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous genetic studies on KB resistance in wheat indicated that one to six major genes condition resistance in various wheat germplasms (Morgunov et al 1994;Fuentes-Dávila et al 1995;Singh et al 1995aSingh et al , b, 1999Villareal et al 1995). Six wheat chromosomes (1D, 2A, 3B, 3D, 5D and 7A) were identified as influencing reaction to the pathogen (Gill et al1993;Singh et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“… Fuentes-Dávila et al (1995) observed higher resistance in lines from the cross “Shanghai#8” and “CMH77.308” possessing three genes with dominant/partially dominant relationship than those with two or with only one gene(s). On a similar note, Singh et al (1995a) reported that digenic genotypes such as “Luan,” “Attila,” “Vee 7/Bow,” “Star,” “Weaver,” “Milan,” “Turacio,” “Opata,” “Picus,” and “Yaco” had a higher level of resistance to KB compared with those with a single gene. These findings imply that pyramiding of multiple genes should lead to expression of KB-free trait and selection for resistance under low levels of disease in artificial epiphytotic conditions should ideally result into the accumulation of resistance genes ( Singh et al, 1995a ).…”
Section: Genetics Of Kb-free Traitmentioning
confidence: 91%
“…On a similar note, Singh et al (1995a) reported that digenic genotypes such as “Luan,” “Attila,” “Vee 7/Bow,” “Star,” “Weaver,” “Milan,” “Turacio,” “Opata,” “Picus,” and “Yaco” had a higher level of resistance to KB compared with those with a single gene. These findings imply that pyramiding of multiple genes should lead to expression of KB-free trait and selection for resistance under low levels of disease in artificial epiphytotic conditions should ideally result into the accumulation of resistance genes ( Singh et al, 1995a ). Given this, the marker assisted selection (MAS) seems to be a technique of choice for accumulating resistance genes in a single cultivar for durable and multi-pathotype resistance not dependent upon creation of artificial epiphytotic conditions.…”
Section: Genetics Of Kb-free Traitmentioning
confidence: 91%
See 2 more Smart Citations